Collaboration, decarbonization, and distributional effects - Mathias Mier; Kais Siala; Kristina Govorukha; Philip Mayer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2022)
We conduct a hybrid scenario exercise to analyze decarbonization pathways of the European power market and related distributional effects across countries as well as between consumers and producers. Our CIB analysis reveals qualitative scenarios that differ in the level of political (stringency of climate policy) and physical collaboration (transmission grid expansion). We use a CGE model to quantify those scenarios for further usage in a power market model. Consumers generally experience considerably higher electricity prices, whereas producers observe higher rents. Electricity prices are lowest in the least collaborative future. Producer rents in turn are highest in the most collaborative one. Patterns hugely differ by country, making 13 countries to profiteers of the least collaborative future and 12 countries to profiteers of the most collaborative one. Only 3 countries profit from medium collaboration. Countries that profit from the most collaborative future experience substantially higher producer rents. Countries that profit from the least collaborative one in turn experience lowest electricity prices.
Keywords: C61; Q40; Q41; Q52; 330; hybrid scenario analysis; CIB method; CGE modeling; energy system modeling; power market modeling; collaboration; decarbonization; energy transition; distributional effects